4(3y-2)+2(3y-2)=

Simple and best practice solution for 4(3y-2)+2(3y-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3y-2)+2(3y-2)= equation:


Simplifying
4(3y + -2) + 2(3y + -2) = 0

Reorder the terms:
4(-2 + 3y) + 2(3y + -2) = 0
(-2 * 4 + 3y * 4) + 2(3y + -2) = 0
(-8 + 12y) + 2(3y + -2) = 0

Reorder the terms:
-8 + 12y + 2(-2 + 3y) = 0
-8 + 12y + (-2 * 2 + 3y * 2) = 0
-8 + 12y + (-4 + 6y) = 0

Reorder the terms:
-8 + -4 + 12y + 6y = 0

Combine like terms: -8 + -4 = -12
-12 + 12y + 6y = 0

Combine like terms: 12y + 6y = 18y
-12 + 18y = 0

Solving
-12 + 18y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 18y = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 18y = 0 + 12
18y = 0 + 12

Combine like terms: 0 + 12 = 12
18y = 12

Divide each side by '18'.
y = 0.6666666667

Simplifying
y = 0.6666666667

See similar equations:

| (u-2)(4+4)= | | 13=0-45x+9 | | -34-2x=11-7 | | 5/11=v/10 | | 5/11=v10 | | 87x-6x=8x+17 | | 87x-6x=8x | | y-(-4)=(-8/9)(x-8) | | 3(4a-7)=5 | | (-7u^2+8u+7)-(2u^2-9u-5)+(-7u^2+5u-7)= | | y-(-2)=(-3/4)(x-5) | | 2x-2=12-52 | | y-(-2)=(3/4)(x-5) | | 25b+20b^3= | | (2x)-(x-4)=5 | | f-(4/1/3)=10 | | 4x+8(x+1)+4=12-4x | | 2x-2(6-4x)=6(x-5)-26 | | f-(41/3)=10 | | 12k+131=3(4k+43) | | 0=-16x^2+40x+2 | | 10(x+2)-2x=2(4x+2)-8 | | 1.2k+2.3=-0.5+7 | | (5u^2+2)-(7u^2-4u+6)= | | 2[3-(6-5r)]-r=-12+3(2+3r) | | (2w^2+3)+(5w^2-4W-6)= | | U/3=12 | | x^2-6x-16/x^2+6x+8 | | (-7u^2+4u-3)+(5u^2+u+6)= | | M/6=8 | | (3t/4) | | (-5v^2+v-3)+(4v^2+6v+2)= |

Equations solver categories